Pilot study of liraglutide effects in non‐alcoholic steatohepatitis and non‐alcoholic fatty liver disease with glucose intolerance in Japanese patients (LEAN‐J). Issue 3 (28th May 2014) - Eguchi, Yuichiro; Kitajima, Yoichiro; Hyogo, Hideyuki; Takahashi, Hirokazu; Kojima, Motoyasu; Ono, Masafumi; Araki, Norimasa; Tanaka, Kenichi; Yamaguchi, Miyuki; Matsuda, Yayoi; Ide, Yasushi; Otsuka, Taiga; et al.
<x xml:space="preserve">Abstract</x> Aim Non‐alcoholic fatty liver disease (NAFLD), a hepatic manifestation of metabolic syndrome, is associated with an increased risk of developing lifestyle‐related diseases including type 2 diabetes, cardiovascular disease and cerebral vessel disease. No current drug therapy provides the ideal effects of decreasing hepatic inflammation while simultaneously improving liver fibrosis. Liraglutide is a glucagon‐like peptide‐1 receptor agonist that affects the histological findings in patients with non‐alcoholic steatohepatitis (NASH). This study was conducted to evaluate the effect and action of liraglutide for biopsy‐proven NASH. Methods After lifestyle modification intervention for 24 weeks, subjects whose hemoglobin A1c levels failed to improve to less than 6.0% and/or whose alanine aminotransferase levels were not lower than baseline, received liraglutide at 0.9 mg/body per day for 24 weeks. Results Of 27 subjects, 26 completed the lifestyle modification intervention. Nineteen subjects received liraglutide therapy for 24 weeks. Body mass index, visceral fat accumulation, aminotransferases and glucose abnormalities improved significantly. Repeated liver biopsy was performed in 10 subjects who continued liraglutide therapy for 96 weeks. Six subjects showed decreased histological inflammation as determined by NASH activity score and stage determined by Brunt classification. We saw no significant adverse events during therapy with liraglutide. Conclusion Our pilot study demonstrated that treatment with liraglutide had a good safety profile and significantly improved liver function and histological features in NASH patients with glucose intolerance.